2016
DOI: 10.1063/1.4941399
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy, band-to-band transitions, phonon modes, and oxidation properties of cobalt-oxide core-shell slanted columnar thin films

Abstract: , band-to-band transitions, phonon modes, and oxidation properties of cobalt-oxide core-shell slanted columnar thin films" (2016). Faculty Publications from the Department of Electrical and Computer Engineering. 349.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…There was no significant evidence of anisotropy in the variable angle spectroscopic ellipsometry (VASE) data. Spectroscopic ellipsometry is an indirect measurement technique, which utilizes changes in polarization of light reflected off or transmitted through a sample [37,38]. An appropriate physical model is necessary to accurately describe the optical properties of the material.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no significant evidence of anisotropy in the variable angle spectroscopic ellipsometry (VASE) data. Spectroscopic ellipsometry is an indirect measurement technique, which utilizes changes in polarization of light reflected off or transmitted through a sample [37,38]. An appropriate physical model is necessary to accurately describe the optical properties of the material.…”
Section: Resultsmentioning
confidence: 99%
“…with best-match parameters of amplitude, A, center energy, E n , and broadening, B r [37]. The real part, ε 1 , is obtained from Kramers-Kronig transformation such that:…”
Section: Resultsmentioning
confidence: 99%
“…Previous analysis reports from single-material SCTFs, core-shell SCTFs 41,43 and SCHTFs 44 introduced the homogeneous biaxial layer approach (HBLA) 38 . The HBLA method assumes that the linear optical response of SC(H)TFs can be described by a single homogeneous layer permitting line-shape function independent wavelength-by-wavelength determination of effective major dielectric functions along three major dielectric polarizability axes, N a , N b , and N c (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…It was observed that the Au nanoparticles increased the anisotropy of the SCTFs 39,40 . Composites of multiple materials can be achieved, for example, by fabrication of core-shell SCTFs using atomic layer deposition 41 , chemical vapor deposition 42 , or post-growth oxidation 43 . Alternatively, in a rather new approach, slanted columnar heterostructure thin films (SCHTFs) can be fabricated by subsequent change of the source material during the GLAD growth (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…36 For example, monoclinic β-Ga 2 O 3 , which has gained attention for high power solid state transistor and switch applications, has been analyzed from the terahertz to the vacuum ultra violet spectral regions for its complete phonon mode and free charge carrier properties, [37][38][39][40] and electronic band-to-band transitions as well as its static and highfrequency dielectric constants, indices of refraction, and extinction coefficients. [41][42][43][44][45] A similar analysis procedure resulted in complete sets of phonon modes for monoclinic scintillator material cadmium tungstate (CdWO 4 ) 46 and YSO. 47 To date, the only generalized spectroscopic ellipsometry investigation of LSO was reported by Jellison et al, and the four real-valued dielectric function tensor spectra were obtained in the spectral range from 200 nm to 850 nm.…”
Section: Introductionmentioning
confidence: 99%